COMPARATIVE EVALUATION OF PHYTOCHEMICAL COMPOSITION AND ANTIOXIDANT POTENTIAL OF SOME MEDICINALLY-IMPORTANT EUPHORBIACEOUS PLANTS - H. Nawaz; M. Aslam; H. Shahzad; F. Mehboob; R. Waheed; R. Jabeen; M. Nawaz; M. Z. Ahmed (Journal of Animal and Plant Sciences, 2022)
The members of the family Euphorbiaceae planted as ornamental plants are rich sources of medicinally important phytochemical antioxidants. The study aimed the comparative evaluation of phytochemical composition and antioxidant potential of different parts of seven different plants of family Euphorbiaceae including Euphorbiahirta, Euphorbiaprostrata, Chrozophoratinctoria,Euphorbia milli, Euphorbia cotinifolia, Euphorbiatirucalli, and Ricinuscommunis. The selected parts of the plants were extracted in 70% methanol and the extracts were subjected to phytochemical screening and phytochemical and antioxidant analysis. The data were statistically analyzed by one-way analysis of variance. The root, stem, and leaves of each of the selected plants consisted of tannins, saponins, flavonoids, and glycosides with few exceptions. The terpenoids and anthocyanins were mostly found in the studied parts of E.tirucalli, and R. communis. The total extract yield, total phemolics, total flavonoids, total tannins, and ascorbic acid content of the extracts ranged from 2.42±0.53 to 10.20±2.02, 0.07±0.01 to 0.34±0.1, 0.07±0.02 to 0.81±0.04, 0.12±0.02 to 0.29±0.05, and 0.17±0.03 to 0.51±0.04 g/100 g dry weight respectively. The content were found to be statistically different (p<0.05) in the studied parts of the selected plants The antioxidant potential in terms of total antioxidant activity, anti-radical capacity, and reducing power was also found to be statistically different (p<0.05) in different parts of the studied plants except for ascorbic acid content of stem. E.tirucalli, R. communis, and E. milli were found to be comparatively good in phytochemical composition while R.communis showed the highest antioxidant potential among the selected plants.
Keywords: Antioxidant potential; Euphorbiaceous plants; Phytochemical composition; Free radical scavenging capacity